Les asymétries frontalières. Contribution à la recherche d’un concept opératoire d’analyse géopolitique de la mondialisation - Fabien Guillot (L'Espace Politique)
This contribution proposes to ask the geopolitics of capitalist globalization and its contemporary transformations based on borders asymmetries. The concept of border asymmetry is placed at the center of the analysis in order to highlight the instrumentalization of borders within the globalized capitalist system. This use of borders asymmetries within the system is one of the conditions allowing the continuation of the accumulation of capital but also the control of spaces, resources and populations. Therefore, it’s possible to understand that border security protectionism is well articulated with free trade and capitalist globalization that use and exploit borders asymmetries in a competitive framework. The transformations produced by globalization are characterized by territorial recompositions, localization strategies, scalar games of actors and processes, but also by the contraction of space-time. In the end, borders asymmetries act as a false contradiction of the geopolitics of globalized capitalism.